Exclusive enteral nutrition provides an effective bridge to safer interval elective surgery for adults with Crohn's disease. Issue 5 (20th January 2017) - Heerasing, N.; Thompson, B.; Hendy, P.; Heap, G. A.; Walker, G.; Bethune, R.; Mansfield, S.; Calvert, C.; Kennedy, N. A.; Ahmad, T.; Goodhand, J. R.
Summary: Background: Few studies have reported the systematic use of exclusive enteral nutrition in the perioperative setting. Aim: To test the hypothesis that exclusive enteral nutrition provides a safe and effective bridge to surgery and reduces post‐operative complications, in adult patients with Crohn's disease requiring urgent surgery for stricturing or penetrating complications. Methods: Patients treated with exclusive enteral nutrition prior to surgery were each matched with two control patients for disease behaviour, type of surgery, age at diagnosis and disease duration. Data on disease phenotype, nutritional status, operative course and post‐operative complications were obtained. Results: Twenty‐five per cent [13/51] patients treated with exclusive enteral nutrition avoided surgery. Exclusive enteral nutrition had no effect on pre‐operative weight, but it significantly reduced serum CRP [median at baseline 36 (interquartile range, IQR: 13–91] vs. pre‐operation 8 (4–31) mg/L, P  = 0.02]. The median (IQR) length of surgery was shorter in patients pre‐optimised with exclusive enteral nutrition than controls [3.0 (2.5–3.5) vs. 3.5 (3.0–4.0) hours respectively, P  < 0.001]. Multivariable logistic regression analysis confirmed that going straight‐to‐surgery compared exclusive enteral nutrition pre‐optimisation was associated with a ninefold increase in the incidence of post‐operative abscess and/or anastomotic leak [OR 9.1; 95% CI (1.2–71.2), P  = 0.04]. Conclusions: Exclusive enteral nutrition frequently down‐stages the need for surgery in patients presenting with stricturing or penetrating complications of Crohn's disease; it is associated with a reduction in systemic inflammation, operative times and the incidence of post‐operative abscess or anastomotic leak. Further trials are needed to elucidate how exclusive enteral nutrition may improve operative outcomes.